Music, emotions and first impression perceptions of a healthcare institutions’ quality: An experimental investigation (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
One of the direct ways of influencing emotions and service quality perceptions is by music stimulation. The purpose of this research is to examine the impact of music of different musical elements (i.e. sad vs. happy music) on respondents' emotions and their first impression perceptions of a healthcare institution's quality. The research was designed as an experimental simulation, i.e. data were collected in an online survey from respondents randomly assigned to evaluate a presentation consisting of multiple images of a healthcare institution in one of three experimental conditions (absence of, happy, and sad music stimulation). The results, in alliance with previous research, demonstrate a relationship between emotions and first impression quality perceptions and between music and emotions, but no relationship between music and first impression quality perception. The obtained significant results yet again emphasize the importance of inducing positive customer emotions as they lead to positive first impression service quality evaluations that subsequently provide appreciated returns. They also stress the importance of carefully choosing music when inducing emotions as music with different musical elements results in different emotional states. One of the limitations of this research is the non-real life situation experimental setting, which is to be overcome in future research.Keywords: Music, healthcare institutions, servqual, fist impression, pleasure, arousal